Receiver Apps Development for Emergency Reporting System Based on Android Platform. Issue 1 (June 2019) - Basyir, M; Mellyssa, W; Suryati, S; Munawar, M
Abstract: Emergency reporting application receiver was built to make emergency services office receive and respond emergency reporting reports easier. User interface of receiver application was designed simply so that users can easily use this application. Recipient application is an android-based application with 4 main pages are login, inbox, history and profile of main service office pages. The reports who sent by sender will go to inbox page, the recipient can respond the report using 2 features, text and phone features. The response given by the recipient will be stored in the response history page. By enabling the GPS feature, receiver's device can directly access the place of sender so recipient can locate the reporter's location easy. This is the main purpose of developing an emergency reporting application, facilitating sender and receiver to get emergency information, so assistance can be provided immediately. Reporting applications can be used by people who connected to internet connections while receiver applications are used by emergency services office such as firefighters, police stations, ambulances, car caches, terrorists and search and rescue (SAR).